Corpus software in EFL teaching: Examination of Language Exposure - Khaitkulov Zakhriddin Xazratkul ugli; Olimboyeva Parizoda Erkinovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
High-quality language education in technical universities requires its interdisciplinary relation to the content of highly specialised subjects corresponding to the training programmes aimed at instructing the future specialists. Educational materials in a foreign language are highly productive if they emphasise the terminology and professional vocabulary authentic to the current state of the scientific field. The aim of the study presented in the article was to assess the validity of the lexical material delivered in the course "English for Business Communicati-on", to determine the selection criteria for this vocabulary as well as the methods for its assimilation and practical application. Methodology and research methods. The applied corpus software enabled to obtain quantitative indicators of the distribution of foreign-language business vocabulary in the given training course. The lexical material being currently offered to students and the professional thesaurus identified via linguistic databases was compared with the use of comparative analysis and synthesis. The lexical units (terms, set expressions), which are the most active in the business sphere, were identified on the basis of its frequency. The authors established the correlation between them and educational vocabulary, both from the perspective of its integration into the course without block concentration throughout the course of university training, and from the perspective of the variety of methods used to practice this vocabulary. It is concluded that the applied educational material needs to be substantially adjusted. The vocabulary does not completely reflect the realities of the business communication sphere and the distribution of active vocational vocabulary regulated by methodological guidelines does not entirely contribute to its strong assimilation